Analisis Faktor Yang Mempengaruhi Perilaku Perempuan Suka Perempuan Pada Narapidana Perempuan di Lembaga Permasyarakatan Kelas IIb Cilacap - Rivani Nur Oktavia; Rakhmat Susilo (Jurnal Ners, 2025)
One form of deviant sexual behavior found among female inmates in correctional institutions is same-sex attraction or lesbian behavior. Contributing factors include family background, lack of religious observance, and peer environment, which have been shown to influence the emergence of same-sex attraction among women. The aim of this study is to analyze the factors influencing same-sex attraction behavior among female inmates at Class IIB Correctional Institution in Cilacap. This study employed a descriptive qualitative method. Data analysis used content analysis. The data collection technique used was non-probability sampling with a snowball sampling approach. Based on interviews, observations, and Focus Group Discussions (FGD) with seven informants, three factors were identified that influence same-sex attraction behavior among female inmates at the Class IIB Correctional Institution in Cilacap: psychological comfort, lack of interaction with the opposite sex, and unpleasant past experiences with men. This study has identified three new factors related to same-sex attraction behavior among female inmates at the Class IIB Correctional Institution in Cilacap.